If `x + y + z = 6sqrt(3)` and `x^2 + y^2 + z^2 = 36`, find `x : y : z`.
\[ \text { If } x+y+z=6 \sqrt{3} \text { and } x^2+y^2+z^2=36 . \text { Find } x: y: z \text {. } \]
Share
Lost your password? Please enter your email address. You will receive a link and will create a new password via email.
Please briefly explain why you feel this question should be reported.
Please briefly explain why you feel this answer should be reported.
Please briefly explain why you feel this user should be reported.
Given:
– \(x + y + z = 6\sqrt{3}\)
– \(x^2 + y^2 + z^2 = 36\)
1. Use the identity \((a + b + c)^2 = a^2 + b^2 + c^2 + 2(ab + bc + ca)\) to expand \((x + y + z)^2\):
\[ (x + y + z)^2 = (6\sqrt{3})^2 \]
\[ x^2 + y^2 + z^2 + 2(xy + yz + zx) = 108 \]
\[ 36 + 2(xy + yz + zx) = 108 \]
\[ 2(xy + yz + zx) = 72 \]
\[ xy + yz + zx = 36 \] (Equation A)
2. Comparing Equation A with \(x^2 + y^2 + z^2 = 36\):
\[ x^2 + y^2 + z^2 = xy + yz + zx \]
This implies that \(x = y = z\), as the sum of the squares of the variables is equal to the sum of their pairwise products.
3. Therefore, the ratio of \(x : y : z\) is \(1 : 1 : 1\).
Conclusion:
The ratio \(x : y : z\) is \(1 : 1 : 1\).